Knowledge, Attitudes and Practices of Colorectal Cancer Screening in Morocco - Errami, Adil Ait; Aouroud, Hala; Krati, Khadija (International Journal of Innovative Research in Medical Science, 2022)
Background: Colorectal cancer (CRC) is a major public health problem. Currently, there are no studies exploring the status of knowledge, attitudes and practices of CRC screening in high-risk populations in Morocco so that effective approaches can be implemented. The objective of the study was: To assess knowledge and awareness of screening methods in the at-risk population. Methods: This was a cross-sectional study where the target population was patients with age >45 years and young people with a history of CRC in the family. Results: 210 subjects were recruited, sex ratio M/F=0.85. Mean age = 53 years, 42% lived in rural area and 38% were illiterate; 86% had a family history of CRC or adenoma and 42% were chronic smokers. 96% reported knowledge of CRC. The most known risk factors: smoking (84.2%), alcoholism (68.5%) while 44.2% knew that colonoscopy was the reference method for screening. Most subjects would like to know more (95.0%). More than 90% agreed that early diagnosis improves prognosis. Finally, 44% will start regular screening. Conclusion: Understanding and recognizing the awareness and attitude regarding CRC screening and the reasons for low screening utilization among high-risk populations could help develop appropriate policies for its prevention and control.